2002
DOI: 10.1074/mcp.m200006-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Approach for Identification of Secreted Proteins during the Differentiation of 3T3-L1 Preadipocytes to Adipocytes

Abstract: We have undertaken a systematic proteomic approach to purify and identify secreted factors that are differentially expressed in preadipocytes versus adipocytes. Using one-dimensional gel electrophoresis combined with nanoelectrospray tandem mass spectrometry, proteins that were specifically secreted by 3T3-L1 preadipocytes or adipocytes were identified. In addition to a number of previously reported molecules that are up-or down-regulated during this differentiation process (adipsin, adipocyte complement-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
187
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(206 citation statements)
references
References 77 publications
16
187
2
1
Order By: Relevance
“…22,23 The upregulation of adipsin gene expression during adipogenesis in this study correlates well with similar observation reported by other research groups. 15,24 PPARg is the most adipose specific of the PPAR subfamily of nuclear hormone receptors, and exists as two isoforms: PPARg 1 and PPARg 2 . It was shown that PPARg regulates the development of adipocyte lineage because its ectopic expression triggers adipogenesis in fibroblast and muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The upregulation of adipsin gene expression during adipogenesis in this study correlates well with similar observation reported by other research groups. 15,24 PPARg is the most adipose specific of the PPAR subfamily of nuclear hormone receptors, and exists as two isoforms: PPARg 1 and PPARg 2 . It was shown that PPARg regulates the development of adipocyte lineage because its ectopic expression triggers adipogenesis in fibroblast and muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Martin et al, 97 have used a combination of ICAT and tandem mass spectrometry to identify and quantitate a comprehensive list of over 500 proteins, which were secreted from neoplastic prostate cancer cell line (LNCaP) in the presence or absence of androgen receptor stimulation. Similar studies have identified numerous secreted proteins during differentiation of 3T3-L1 preadipocytes to adipocytes, 98 in response to calcium-dependent secretion in human neutrophils, 99 during osteoclast differentiation 100 and astrocytes. 101 Cell surface proteome Proteomic approaches for the comprehensive profiling and identification of proteins on cell surface or membranes have been reported.…”
Section: Secretomementioning
confidence: 79%
“…Investigations aimed at characterizing adipose tissue samples frequently employ LC- MS-based methods in combination with gel-based proteomics due to the high lipid content and low protein amount of the adipose tissue [6,7,10,12,14]. To overcome these challenges, in our previous investigations we identified a detergent-free protein extraction method directly compatible with subsequent 2D-LC-MS/MS analysis [16].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations aimed at uncovering modifications in WAT protein expression are of important clinical interest in the quest to identify new therapeutic targets or candidate biomarkers for these prevalent pathologies [4,5]. Scientific prominence of adipose tissue proteomics along with an increasing number of adipose tissue proteomics studies per year [6][7][8][9][10][11][12][13][14] was recently observed by Peinado and coworkers [15]. The main hurdles in the isolation and identification of adipose tissue proteins are its high lipid content combined with low protein amount and a high proteome complexity related to significant tissue vascularization and the presence of a multitude of functionally important cell types located in different tissue fractions [4,16,17].…”
mentioning
confidence: 99%